Performance of a solar-assisted solid desiccant dryer for oil palm fronds drying. (July 2016) - Misha, S.; Mat, S.; Ruslan, M.H.; Salleh, E.; Sopian, K.
Highlights: The use of desiccant material and solar energy produces good drying air condition. The solar energy contributes about 66% from the total energy used by the dryer. The drying rate of oil palm fronds using dryer is higher than open sun drying. The drying efficiency and pick up efficiency of solar dryer is high at full load. The developed solar dryer also can be utilized to dry any agricultural products. Abstract: A solar-assisted solid desiccant dryer was used to dry crushed oil palm fronds. Solar energy was used to heat water with a solar collector and heat was transferred to the air through two heat exchangers. The hot air is used for regeneration of desiccant wheel and increase temperature of drying air after dehumidification. Drying time for reducing the moisture content of crushed oil palm fronds from 69% to 29% under open sun drying was approximately 30 h and 40 min. Drying time was reduced by approximately 64%, 44%, and 33% for products in the first, second, and third columns of the developed solar dryer, respectively. Drying efficiency at full capacity was 19%, and 65% of the energy used was solar energy. Drying and pick-up efficiencies declined as the moisture content of the products decreased and less quantity of product in the drying chamber. The drying rate at full capacity was 8.37 kg/h, which is twice that of open sun drying (4.23 kg/h). Drying using semi-continuous mode was performed to reduce the drying time. The desiccant wheel contributed to improving drying air quality with sensible and latent effectiveness of 74% and 67%, respectively. The combination of desiccant and solar dryer produced better drying air condition, improved drying performance and consumed low electrical energy because solar energy was used as a primary energy source.